Kelayakan Asnaf Fakir Miskin Sebagai Penerima Zakat Berdasarkan Had Kifayah - Gustani Gustani; Siti Rohmah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
Had kifayah is the sufficiency limit or basic standard of individual/family needs plus the adequacy of existing dependents as an effort to determine the eligibility of needy mustahik zakat recipients according to regional and local socio-economic conditions. This study aims to calculate the amount of kifayah had in Cirebon, Indramayu, Majalengka, and Kuningan (Ciayumajakuning). The method of calculating had kifayah refers to the had kifayah study issued by the PUSKAS BAZNAS, consisting of 7 dimensions: food, clothing, housing, household facilities, worship, education, and health, and transportation. Sources of data used are primary and secondary data obtained through documentation, interviews, and observations. Based on the calculation results, the average amount of had kifayah in Ciayumajakuning around is IDR 2,977,187 per household per month, and the average amount of kifayah has per capita is IDR 832,853 per month.